THE ABILITY OF FAST-GROWING TRANSGENIC AFRICAN CATFISH (Clarias gariepinus) ON PREDATOR AVOIDANCE - Huria Marnis; Bambang Iswanto; imron imron; selny Febrida; Raden Roro Sri Pudji Sinarni Dewi (Indonesian Aquaculture Journal, 2016)
Research Institute for Fish Breeding has produced transgenic African catfish (Clarias gariepinus) containing stripped catfish growth hormone gene (PccBA-PhGH) with growth 19.86% faster than that of non-transgenic fish. This fish has high potential to be released and utilized for fish farming sector to increase national production. However, there is not yet information about environmental risk of this fish. One of the major fitness traits determining potential environmental risk is predator avoidance. This study aimed to determine the predator avoidance ability of transgenic African catfish in an experimental laboratory condition. In this study, thirty five individuals each of transgenic and non-transgenic with body weight of about 0.1 ± 0.019 g were communally stocked in 60 cm x 40 cm x 40 cm aquarium with limited feeding frequency (ad libitum twice a day). One day after the fish were stocked, the predators were added to each aquarium. The non-transgenic and transgenic with body weight of 1.0 ± 0.024 g were stocked as predators as many as five individual in each aquarium. After approximately two weeks of predation, all remaining fish were collected for transgenic verification by PCR method. Genomic DNA was isolated from fin tissue of individually survivors. The results of this study showed that the transgenic fish had worse predator avoidance and lower cannibal than non-transgenic (P<0.05). There was no significant difference in growth performance between transgenic and non-transgenic African catfish (P>0.05) in limited food. The transgenic fish may have lower fitness than non-transgenic.